Motives for taking part in physical activites based on gender / Vincent A. Parnabas ... [et al.] - A. Parnabas, Vincent; Abdullah, Nagoor Meera; Mohamed Shapie, Mohamad Nizam; Abdul Rahim, Mohamad Rahizam (Universiti Teknologi MARA, 2022)
There are many reasons why individuals participate in sports or physical activities. There are two main types of motives for engaging in physical activities, which is intrinsic and extrinsic motivation. Previous research found that the six important motives, given by student-athletes for sport participation, were achievement, body shape, physical fitness, teamwork, learning new skills and challenges. However, research comparing the difference on motives for taking part in physical activities, especially on gender is limited. The aim of this study is to find the motives of taking part in physical activities among male and female student-athletes. A hundred student-athletes Purpose of Sport Questionnaire. Seven factors were derived from the questionnaire, Mastery or Cooperation, Physically Active lifestyle, Good Citizen, Competitiveness, High Status Career, Enhance Self-Esteem and Social Status or Getting Ahead. The sample was chosen from a Malaysian university. The result showed that there isn't any significance differences on the motives of taking part in physical activity between genders. Since the result showed that the main motive for both gender were physically active lifestyle, it is better to plan the facilities of sport to fulfill this motive. In addition, identifying the range of motives given by the result of this study, will help sports psychologists to provide adequate and variety of sports programmers to maintain interest among participants.